Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7320104
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis of EEG in major depression with fractal dimensions

Abstract: Major depressive disorder (MDD) is a psychiatric mood disorder characterized by cognitive and functional impairments in attention, concentration, learning and memory. In order to investigate and understand its underlying neural activities and pathophysiology, EEG methodologies can be used. In this study, we estimated the nonlinearity features of EEG in MDD patients to assess the dynamical properties underlying the frontal and parietal brain activity. EEG data were obtained from 16 patients and 15 matched healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…In addition, subjects performing emotion-related tasks in major depression can show decreased frontal cortex gamma 23,24 . Akar et al 20 found increased resting complexity of gamma signaling in frontal and parietal cortex, in subjects with major depression. Given the task- and anatomy-specific nature of gamma band activity shown in rodent work, it is highly likely that this heterogeneity in the human literature reflects the varying conditions used in different studies.…”
Section: Gamma Rhythms In Depressive Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, subjects performing emotion-related tasks in major depression can show decreased frontal cortex gamma 23,24 . Akar et al 20 found increased resting complexity of gamma signaling in frontal and parietal cortex, in subjects with major depression. Given the task- and anatomy-specific nature of gamma band activity shown in rodent work, it is highly likely that this heterogeneity in the human literature reflects the varying conditions used in different studies.…”
Section: Gamma Rhythms In Depressive Disordersmentioning
confidence: 99%
“…The experimental approaches used in these studies vary, with some measuring gamma power during cognitive tasks 18,19 , and others analyzing the oscillatory power spectrum at rest (i.e., baseline) 20–22 . These studies have used various gamma frequency sub-bands, anatomical regions and behavioral states ranging from memory or emotional tasks, to sensory-evoked measures, and not surprisingly have yielded varying results.…”
Section: Gamma Rhythms In Depressive Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the difficulty to detect changes in physiological EEG features through traditional lineal methods has been reported [17]. Otherwise, EEG recording approach presents some advantages over the rest of biosignals due to the standardization of the electrode placement on the scalp (10-20 system), guaranteeing the reproducibility of the experiments and the comparison among different studies.…”
Section: Measuring Emotional Statesmentioning
confidence: 99%